ABDOMINAL AORTA INJURY-A FATAL COMPLICATION OF LAPAROSCOPIC CHOLECYSTECTOMY - Jamil, Muhammad; Usman, Rashid (Journal of Ayub Medical College Abbottabad, 2015)
Laparoscopic cholecystectomy (LC) has many advantages over open cholecystectomy, but sometimes, it can cause life threatening complications. Abdominal aortic injuries are rare but if occur, usually prove fatal if not diagnosed and treated promptly. We report a case of abdominal aortic injury which occurred during laparoscopic cholecystectomy. To the best of our knowledge this would be the first ever case reported in Pakistan